The new mestizas: activist consciousness against femi(ni)cide in diasporic collectives formations during Mexico’s #8 and #9M 2020 - Ibáñez O'Donnell, Sara (HeLix, 2025)
A mass women’s march took place across Mexico’s cities on Sunday 8th March 2020 (#8M), directly followed by Mexico’s first ever nationwide women strike (#9M/ #UnDíaSinNosotras) the next day. Both these events deeply resonated transnationally. Open calls were disseminated through digital networked umbrella platforms appealing to Mexican women around the world to publically demonstrate against gender-based violence and femi(ni)cide impunity. The encounters that resulted from these led to new feminist collective formations hosting a wide range of lived experiences. And those encounters became, in turn, new potential spaces of belonging for activist consciousness to flourish in their diasporic context. This article draws on Gloria E. Anzaldúa's concept of mestiza consciousness to reflect on the formation of two such groups in London and Berlin and on their emerging narratives at the time.